How power moves: A Foucauldian analysis of (in)effective coaching - Mills, J. P.; Denison, J. (International Review for the Sociology of Sport, 2018)
Knowing how to coach effectively is one ever-present truth across all sports and yet our previous research based on the work of Michel Foucault has illustrated how the effectiveness of endurance running coaches` everyday coaching practices is limited by their use of various disciplinary techniques. Missing from these analyses was any consideration of Foucault`s conceptualization of how modern power works through the disciplinary instruments or the confession to progress coaches` practices. To address this gap in this paper, we present data from interviews and observations with 15 male high-performance endurance running coaches in the United Kingdom and the United States to examine how the exercise of disciplinary instruments along with the confession affects endurance running coaches` understanding of how to coach. In our analysis we show how discipline`s instruments and the confession operate in ways that significantly restrict and limit endurance running coaches` efforts to develop their athletes and progress their practices. In order to develop effective coaches it is therefore essential that coaches become aware of how power operates in and around their coaching environment.